The association between sociodemographic and clinical characteristics and poor glycaemic control: a longitudinal cohort study. Issue 11 (6th December 2015) - McBrien, K. A.; Manns, B. J.; Hemmelgarn, B. R.; Weaver, R.; Edwards, A. L.; Ivers, N.; Rabi, D.; Lewanczuk, R.; Braun, T.; Naugler, C.; Campbell, D.; Saad, N.; et al.
Abstract: Aims: People with diabetes and poor glycaemic control are at higher risk of diabetes‐related complications and incur higher healthcare costs. An understanding of the sociodemographic and clinical characteristics associated with poor glycaemic control is needed to overcome the barriers to achieving care goals in this population. Methods: We used linked administrative and laboratory data to create a provincial cohort of adults with prevalent diabetes, and a measure of HbA1c that occurred at least 1 year following the date of diagnosis. The primary outcome was poor glycaemic control, defined as at least two consecutive HbA1c measurements ≥ 86 mmol/mol (10%), not including the index measurement, spanning a minimum of 90 days. We used multivariable Cox proportional hazards models to evaluate the association between baseline sociodemographic and clinical factors and poor glycaemic control. Results: In this population‐based cohort of 169 890 people, younger age was significantly associated with sustained poor glycaemic control, with a hazard ratio (HR) of 3.08, 95% CI (2.79–3.39) for age 18–39 years compared with age ≥ 75 years. Longer duration of diabetes, First Nations status, lower neighbourhood income quintile, history of substance abuse, mood disorder, cardiovascular disease, albuminuria and high LDL cholesterol were also associated with poor glycaemic control. Conclusions: Although our results may be limited by the observational nature of the study, the large geographically defined sample size, longitudinal design and robust definition of poor glycaemic control are important strengths. These findings demonstrate the complexity associated with poor glycaemic control and indicate a need for tailored interventions. What's new?: We used linked laboratory and administrative data for a large geographically defined cohort of over 160 000 people with diabetes to determine the association between sociodemographic and clinical characteristics and poor glycaemic control, defined as sustained HbA1c ≥ 86 mmol/mol (10%). We used a longitudinal study design with up to 8 years of follow‐up. We found that younger age was the strongest predictor of poor glycaemic control. Other sociodemographic factors (First Nations status and low socio‐economic status), psychiatric disorders and clinical factors including cardiovascular disease, albuminuria and dyslipidaemia were also associated with the outcome of poor glycaemic control.